2015
DOI: 10.3892/or.2015.3866
|View full text |Cite
|
Sign up to set email alerts
|

miR-141 confers docetaxel chemoresistance of breast cancer cells via regulation of EIF4E expression

Abstract: Abstract. Resistance to docetaxel, a chemotherapy drug for breast cancer (BC) treatment, occurs in ~50% of patients, and the underlying molecular mechanisms of drug resistance are not fully understood. Gene regulation through miR-141 has been proven to play an important role in cancer drug resistance. The present study investigated the role of miR-141 expression in BC cells of acquired docetaxel resistance. Inhibition of miR-141 enhanced the response to docetaxel in docetaxel-resistant cells (MCF-7/DTX and MDA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 39 publications
0
30
0
1
Order By: Relevance
“…Drug resistance has severely restricted the application of chemotherapy and neoadjuvant chemotherapy, resulting in treatment failure. Therefore, various researchers have focused on the mechanism of chemotherapy resistance in breast cancer (11)(12)(13). Emerging evidences has indicated that the tumor microenvironment serves an important role in carcinogenesis and development, which has also been identified to participate in therapeutic resistance (14)(15)(16).…”
Section: Discussionmentioning
confidence: 99%
“…Drug resistance has severely restricted the application of chemotherapy and neoadjuvant chemotherapy, resulting in treatment failure. Therefore, various researchers have focused on the mechanism of chemotherapy resistance in breast cancer (11)(12)(13). Emerging evidences has indicated that the tumor microenvironment serves an important role in carcinogenesis and development, which has also been identified to participate in therapeutic resistance (14)(15)(16).…”
Section: Discussionmentioning
confidence: 99%
“…3). These MDA-MB-231/Taxol cells also present increased expression of miR-141 [46], which was shown to regulate expression of eukaryotic translation initiation factor 4E, which was involved in breast tumor cell cycle progression (Fig. 3).…”
Section: Micrornas and Taxanes Resistancementioning
confidence: 92%
“…& ,[41][42][43][44][45][46][47][48][49][50][51][52][53][54]. MiRNAs that inhibit P-gp, such as miR-451, miR-320a, and miR-298 are implicated in ADR resistance(Fig.…”
mentioning
confidence: 98%
“…miR-141 overexpression contributes to acquired chemoresistance, for both in vitro and in vivo models. The initiation factor 4E (EIF4E) mRNA is a target of miR-141, that is involved in drug-induced apoptosis, conferring resistance to docetaxel-sensitive BC cells (155). miR-141 regulates cisplatin sensitivity in non-small lung cancer cells via PDCP4 inhibition and its inhibition increases cisplatin-induced apoptosis (156).…”
Section: A Network Analysis: the Most Central Ncrnas In Chemoresistancementioning
confidence: 99%